2010
DOI: 10.5326/0460132
|View full text |Cite
|
Sign up to set email alerts
|

Intraaxial Spinal Cord Hemorrhage Secondary to Atlantoaxial Subluxation in a Dog

Abstract: A 1-year-old, 3.5-kg, spayed female, toy poodle was presented for acute-onset tetraplegia and neck pain. Neuroanatomical diagnosis was consistent with a first through fifth cervical (C(1) through C(5)) spinal cord lesion. Radiographs of the cervical vertebral column revealed atlantoaxial (AA) subluxation. Magnetic resonance imaging revealed abnormalities consistent with intraaxial spinal cord hemorrhage at the level of the AA articulation. The dog was treated with external coaptation. After 8 days, the dog reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 40 publications
1
20
0
1
Order By: Relevance
“…In fact, considering literature data regarding the treatment of AA instability in toy breeds, conservative options and several surgical stabilisation techniques are described [1,2,10,12,13,15,19,26]. Standard surgical treatment consists of ventral arthrodesis with cross pinning, transarticular lag screw fixation or vertebral plating [1,12,19,21,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, considering literature data regarding the treatment of AA instability in toy breeds, conservative options and several surgical stabilisation techniques are described [1,2,10,12,13,15,19,26]. Standard surgical treatment consists of ventral arthrodesis with cross pinning, transarticular lag screw fixation or vertebral plating [1,12,19,21,24].…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of the aetiopathogenesis, AA instability causes acute and/or chronic spinal cord compression [1,2]. Secondary lesions typically develop in affected individuals including spinal cord compression, contusions or haemorrhage which can predispose to hydromyelia, focal or diffuse syringohydromyelia and gliosis [9,15,17,26]. The principal radiographic sign of AA subluxation is enlargement of the space between the tip of the spinous process of the axis and the dorsal arch of the atlas [26] on laterolateral radiography.…”
Section: Introductionmentioning
confidence: 99%
“…Presence or absence of deep pain sensation and findings on magnetic resonance (MR) images are significant information in prognostic evaluation of dogs with an acute-onset of tetraplegia/tetraparesis secondary to atlantoaxial subluxation [16,34,35]. Nevertheless, it may be difficult to make a certain prognosis and thereby hard to recommend euthanasia versus surgical treatment and rehabilitation of such dogs.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study including MR images of 100 human patients with a traumatic cervical spinal cord injury, Miyanji et al [37] found that hemorrhage, swelling and maximum compression of the spinal cord were associated with a poor prognosis for neurologic recovery. In a one-year-old toy poodle dog presented for acute-onset tetraplegia and given a guarded prognosis for full neurological recovery, Kent et al [34] chose conservative treatment with external coaptation for eight days before re-examining the dog and evaluating the prognosis. In the present study, both dogs showed irreversible lesions in the atlantoaxial region of the spinal cord consisting of necrosis, loss of neural parenchyma and infiltration of gitter cells.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Equally, SIEH and hematomyelia are 2 rare clinical entities in veterinary medicine. 13,14 Intramedullary hemorrhage may develop in dogs with suspected spontaneous bleeding, arteriovenous malformation, or myelomalacia. 13,14 Intramedullary hemorrhage may develop in dogs with suspected spontaneous bleeding, arteriovenous malformation, or myelomalacia.…”
Section: Commentsmentioning
confidence: 99%